Community-Academic Peer Review: Prospects for Strengthening Community-Campus Engagement and Enriching Scholarship (Engaged Scholar Journal: Community-Engaged Research, Teaching, and Learning, 2019)
Scholarly peer review is hailed as an indispensable process to maintain quality and rigour in research publications. However, there is growing recognition of the limitations of peer review and concerns about the unexamined assumptions surrounding the processes that favour academic ways of knowing. In this paper, we build on these debates by exploring the possibilities for engaging communities in shaping and assessing the value of knowledge. Drawing on insights of a community-academic peer review pilot project through a pan-Canadian research partnership, we reflect on the value of incorporating community perspectives into research review processes and challenges of scaling-up these efforts. We argue that the perspectives of community-based practitioners are a necessary part of peer review—especially for Community-Based Research—to increase validity and accountability. This process gives academics and practitioners the power to collectively assess and evaluate knowledge products. Fundamentally, these efforts are about reviving higher education and critical research as part of a democratic public sphere that is open, inclusive, and relevant. We conclude by reflecting on the value of incorporating community perspectives into the peer review process. We also offer recommendations on how to recognize and incorporate community knowledge and experiences into assessment structures.